Immunomodulators targeting the PD‐1/PD‐L1 protein‐protein interaction: From antibodies to small molecules. Issue 1 (14th September 2018) - Yang, Jeffrey; Hu, Longqin
Abstract: Cancer immunotherapy has made great strides in the recent decade, especially in the area of immune checkpoint blockade. The outstanding efficacy, prolonged durability of effect, and rapid assimilation of anti‐PD‐1 and anti‐PD‐L1 monoclonal antibodies in clinical practice have been nothing short of a medical breakthrough in the treatment of numerous malignancies. The major advantages of these therapeutic antibodies over their small molecule counterparts have been their high binding affinity and target specificity. However, antibodies do have their flaws including immune‐related toxicities, inadequate pharmacokinetics and tumor penetration, and high cost burden to manufacturers and consumers. These limitations hinder broader clinical applications of the antibodies and have heightened interests in developing the alternative small molecule platform that includes peptidomimetics and peptides to target the PD‐1/PD‐L1 immune checkpoint system. The progress on these small molecule alternatives has been relatively slow compared to that of the antibodies. Fortunately, recent structural studies of the interactions among PD‐1, PD‐L1, and their respective antibodies have revealed key hotspots on PD‐1 and PD‐L1 that may facilitate drug discovery efforts for small molecule immunotherapeutics. This review is intended to discuss key concepts in immuno‐oncology, describe the successes and shortcomings of PD‐1/PD‐L1 antibody‐based therapies, and to highlight the recent development of small molecule inhibitors of the PD‐1/PD‐L1 protein‐protein interaction.